2014
DOI: 10.1103/physrevapplied.2.044016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Temperature Distributions in Stacks of Intrinsic Josephson Junctions inBi2Sr2CaCu2

Abstract: We study the universal relationship between the hot-spot size and the intensity of terahertz emission from intrinsic Josephson junctions by dynamically controlling the temperature distributions in mesas of Bi 2 Sr 2 CaCu 2 O 8þδ . The uniform current bias leads to a significant increase in local temperature compared to the nonuniform current bias. The thermal response of emission differs between the high-and low-bias regimes. We find a strong positive correlation between the emission intensity and the volume o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
(35 reference statements)
1
38
0
Order By: Relevance
“…For sufficiently low bias currents, the temperature rises only slightly to values above the bath temperature T bath and the voltage V across the stack increases with increasing bias current I. With increasing I and input power the currentvoltage characteristics (IVCs) start to back-bend and, at some bias current in the back-bending region, a hot spot forms in the stack 3,6,8,13,18,[21][22][23]25,26,34,68 , creating a region heated to temperatures above the critical temperature T c . Similar effects also occur in other systems 69,70 .…”
Section: Introductionmentioning
confidence: 99%
“…For sufficiently low bias currents, the temperature rises only slightly to values above the bath temperature T bath and the voltage V across the stack increases with increasing bias current I. With increasing I and input power the currentvoltage characteristics (IVCs) start to back-bend and, at some bias current in the back-bending region, a hot spot forms in the stack 3,6,8,13,18,[21][22][23]25,26,34,68 , creating a region heated to temperatures above the critical temperature T c . Similar effects also occur in other systems 69,70 .…”
Section: Introductionmentioning
confidence: 99%
“…13 More recently, we have reported that the hotspots are detrimental for emission intensities. 14 The emission frequency f e is tuned by changing either the bias current or bath temperature T b . Benseman et al investigated the temperature dependence of the emission frequency in asymmetric device configuration, namely, a superconducting substrate overlain with a trapezoidal stack.…”
Section: Introductionmentioning
confidence: 99%
“…The unique (sub-) THz source based on a single-crystalline mesa structure of the high transition-temperature T c superconductor Bi 2 Sr 2 CaCu 2 O 8+ δ (Bi2212) was first reported in 200716, and its subsequent development has proceeded rapidly171819202122232425262728293031323334353637383940414243444546. Output radiation powers of a few tens of μ W have been consistently achieved from single conventional mesas3743,44, and of about 600  μ W was reported from a synchronized conventional three-mesa array45, and the radiation frequency could be varied almost continuously between 0.3 and 2.4 THz from a stand-alone mesa sandwich device46.…”
mentioning
confidence: 99%